JOYBARDÍŃ TARMAQ GRAFIGIN JARATÍW ALGORITMI - Abdullaev, A.; Srajova, U.D. (SCIENCE and SOCIETY, 2026)
This article presents an algorithm for developing a network graph for designing complex tasks. The network graph teaches the main indicators of the task, the necessary work paths, and the completion time.